Dark Personality in the Workplace: Introduction to the Special Issue. Issue 1 (January 2015) - Schyns, Birgit
<x xml:space="preserve">Abstract</x> This introduction to the Special Issue on Dark Personality in the Workplace outlines the nature of dark personality and why it is relevant in the workplace. In addition, it reviews the articles of the special issue in terms of both their findings and the lessons that can be drawn from them in order to enhance our understanding of dark personality in the workplace. Finally, suggestions are made concerning future directions for research on dark personality in the workplace